Centro de atenção psicossocial : perfil epidemiológico dos usuários - Souza, Adriano Rodrigues de (2007)
This research objectified to outline the epidemiological and socio-economical profile of the Centre of Psychosocial Attention (CAPS)’s users in the municipality of Fortaleza, Ceará, based on their handbooks. It was an epidemiological study which was carried out in three CAPS located in Regional Executive Secretariats (SER III, IV and VI). The data was produced through the elaboration of a questionnaire which included the following aspects: identification and socio-demographical data, personal previous history, family previous history, pathological previous history, symptomatology, types of therapeutic activities and evolution. Based on 385 handbooks, the users’ profile was built up. Socio-demographical profile: 60,1% were female; 63,4% of the patients were between 20 and 49 years old; 43,9% of the patients finished Junior high school; 69,5% have an income between 1 and 4 minimal wages; 15,4% have the pension from the retirement as the main income; 71,9% are Catholics; 92,6% live in houses. Personal, familiar and pathological record: 40,5% presented psychical alterations in their childhood; 45,4% of the studied patients’ parents presented a psychical alteration during the life; 60% of the studied patients presented conflicts in familiar relationship; 53,9% have been interned in clinical hospitals; 15,9% had the insomnia as the main symptomatologic complaint; 18,5% of the patients had as the main factor of the crises, a beloved’s death; 39,4% had Neurotic Disturbances as the main diagnosis; 91% of the cases had the psychopharmacos as the main chosen treatment; 30,5% used the ansiolitics as the first chosen drug; 56% of the patients had other forms of approach such as individual attendance; in 9% of the cases, this attendance was carried out by a psychologist. From the obtained data we can conclude that: most users are female; the age group considered productive was present with more than 60% in both genders; most part of the patients who frequent the CAPS have low income, primary education, live with pension from retirement and more than 90% live in houses; more than 40% had disturbances in other phases of life; more than 50% have been interned in clinical hospitals; most of them has insomnia as the main symptomatologic complaint and 91% had the psychopharmacology as the only form of treatment. Considering the data, we can infer that CAPS takes shape of the structure of attention to people that present any kind of mental suffering, what is recognized by the health team itself. But we can also infer that the principles of the Psychiatric Reform were not always attended, considering this service as one of the provisions of the net of mental health attention. This type of service objectifies to actuate as a strategic provision in the building of the community net of care, developing community therapeutic projects turned to the integral attention to the users and their families, propitiating integration between health services, users, community and social net of support (BRASIL 2004). Through the results of this study, it is considered that a lot must be reviewed by managers and workers of the net of mental health attention, trying to advance in the achievements which were achieved up to now and guaranteed by Law. The building of a new net of mental health attention is more than the mere amplification in the number of services. It requires the building of new knowledge and practices based on the paradigm proposed by the Psychiatric Reform, changing the focus of attention from the disease to the person in mental suffering, in all the complexity resulting from this condition. Although this study contemplates only three services, the reality showed here provides subsidy to rethink the CAPS as an important provision in the implementation of the net of mental health attention in Ceará.